REIMAGINING NEOLIBERALISM, GLOBALIZATION, LITERATURE AND LANGUAGE EDUCATION: AN INTERVIEW WITH PROF. DR. DIANA BRYDON / Reimaginando o neoliberalismo, a globalização, a literatura e a educação linguística: uma entrevista com Prof. Dr. Diana Brydon - Brydon, Diana; Ferraz, Daniel de Mello (Universidade do Estado do Rio de Janeiro, 2019)
In this interview, Dr. Brydon insightfully discusses contemporary keywords such as neoliberalism and globalization and how they intersect with literary studies and language education. She also talks about the transnational literacies projects developed between Canada and Brazil along the past ten years. Dr. Brydon also discusses the dichotomy between literature and language/linguistic studies by suggesting the reimagination of both fields. In the case of literature, she introduces speculative literature as a possibility to (re)imagine “horrific dystopian worlds” – on one hand, and a “world where people value negotiation, compromise, and solutions that may not be ideal to any of the partners but that are livable for all of us” – on the other.